Sabores e segredos. Receituários Conventuais Portugueses da Época Moderna - Isabel Drumond Braga (DIAITA, 2015)
This work consists of the transcription, analysis and interpretation of two unpublished eighteenth-century conventual recipes, which were compared with other counterparts in near periods, produced within the same scope and among the laity. The course undertaken aimed at assessing the real or imaginary originality of the recipes prepared in religious houses of the Modern Age and permitted to answer several questions, namely: the extent to which the conventual recipes were created in this scope or were taken to the monasteries by nuns, friars, monastic nuns, monks, maids and servants? Since the ingredients and cooking techniques used in religious houses were known in the places where lay people were, especially among confectioners, whose regiments were clear about the requirements to obtain letter, how can we explain the frenzy, often excessive, the conventual designation applied to so many and so frenetic recipes? In fact monks, monastic nuns, nuns, friars, maids and servants had time to cook and it is possible that many, or at least some, appreciated the preparation of savoury dishes and especially sweets. However, wasn't the offer and commerce of sweets the most responsible for the exaltation of the conventual designation, in the absence of pastries taking place in the 17th and 18th centuries, and confectioneries whose fame would spread out to the Kingdom? Are we dealing with the creation of truly conventual sweets or sheer preparations of recipes originally produced in the kitchens of big houses and subsequently taken to the monasteries, such as so many other meat and fish recipes? The analysis and the interpretation of the sources made very clear that the overwhelming majority of the recipes prepared in religious houses was hardly original, we just have to compare these recipes with those circulating both handwritten and printed in other recipe books of the time. On the other hand, the alleged secrecy that should involve the aforementioned conventual recipes - and this is evident in some female recipe books - was broken, in such a manner that lay cookbooks include recipes with names of some religious houses, which does not necessarily mean these recipes have originated there but that they were prepared successfully there and the subject of appreciation by those who had the opportunity to taste them.